Efeitos do canal de crédito na transmissão de política monetária: comparação empírica entre Brasil e Estados Unidos - Dias Junior, Paulo Henrique (2011)
This research aims to analyze the influence of asymmetric information in credit markets and identify their implications in the transmission of monetary policy in countries with different institutional and regulatory frameworks. The arguments and the empirical evidence presented in this study are intended to identify the importance of transmission channels of monetary policy as additional mechanisms for the monetary policy. One of these analyses considers the effects of financial structure and institutional environment in access to bank loan market, which may influence the effectiveness of credit channels and transmission mechanisms of monetary policy. Applying the vector autoregressive (VAR) and the markov-switching vector autoregressions (MS-VAR) methodologies to identify that the results are consistent with the theory of the “credit view”, which describes the increasing the information asymmetric problems associated with the difficult access to the bank loans in periods of credit constraint. These behaviors exhibited by the credit models suggest that financial regulatory and institutional framework determine the sensitivity of credit to monetary innovations and different economies react to monetary policy shocks.